Selective isolation of Arctic marine actinobacteria and a down-scaled fermentation and extraction strategy for identifying bioactive compounds - Schneider, Yannik K.; Hagestad, Ole C.; Li, Chun; Hansen, Espen H.; Andersen, Jeanette H. (Frontiers in Microbiology, 2022)
Actinobacteria are among the most prolific producers of bioactive secondary metabolites. In order to collect Arctic marine bacteria for the discovery of new bioactive metabolites actinobacteria were selectively isolated during a research cruise in the Greenland Sea, Norwegian Sea and the Barents Sea. In the frame of the isolation campaign, it was investigated how different sample treatments, isolation media and sample-sources, such as animals and sediments, affected the yield of actinobacterial isolates to aid further isolation campaigns. Special attention was given to sediments, where we expected spores of spore forming bacteria to enrich. Beside actinobacteria a high share of bacilli was obtained which was not desired. An experimental protocol for down-scaled cultivation and extraction was tested and compared with an established low-throughput cultivation and extraction protocol. The heat-shock method proved suitable to enrich spore-, or endospore forming bacteria such as bacilli. Finally, a group bioactive compounds could be tentatively identified using UHPLC-MS/MS analysis of the active fractions.